Control of Photon-Magnon Coupling in a Planar Hybrid Configuration - Verma S.; Maurya A.; Singh R.; Bhoi B. (My University, 2025)
Photon-magnon coupling (PMC) integrates microwave or optical photons with magnons, aiming to exploit their distinct strengths in a unified hybrid quantum system, for potential applications in quantum information science and technology. By utilizing numerical simulations, we design a planar hybrid system comprising a hexagonal-ring resonator (HRR) and yttrium iron garnet (YIG) thin film to explore the interaction between microwave photons and magnons. The anti-crossing effects between the HRR’s photon mode and the YIG’s magnon modes were observed in |S21|-frequency plots under various externally applied magnetic fields. An equivalent theoretical model, based on coupled oscillators, accurately replicated the observed anti-crossing effect and provided estimates for the PMC strength. Furthermore, we explored the behavior of the photon-magnon interaction by altering the position of the YIG film on the HRR’s track width, allowing for a more reliable control of the PMC strength variable within the range of 38.78 to 126.6 MHz (nearly 200%) in the planar-geometry HRR/YIG hybrid system. This study opens avenues for designing novel hybrid systems with effective control over the strength of PMC in a planar geometry. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.